Virtual Reality Sebagai Media Distraksi Dalam Menurunkan Nyeri Pada Anak Pasca Operasi Apendisitis - Eva Oktaviani; Nadi Aprilyadi; Memy Suci Ramadanti (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: Globally, the incidence of appendicitis is approximately 100–150 per 100,000 population and remains one of the most common causes of abdominal surgery in children. The use of Virtual Reality (VR) as a non-pharmacological distraction technique in managing postoperative pain after appendectomy is still limited, particularly in nursing practice in Indonesia. Poorly managed pain can lead to physical disturbances, increased anxiety, behavioral changes, and delayed recovery. In addition to pharmacological therapy, pain can also be managed through non-pharmacological methods such as distraction techniques, including VR, which provides an immersive visual experience to divert children’s attention from pain. Objective: This study aims to describe the application of VR-based distraction media in reducing pain intensity in children after appendectomy. Methods: This study used a case study approach involving two pediatric patients who had undergone appendectomy. The nursing diagnosis established was acute pain. The intervention involved the use of entertainment-based VR for 10–15 minutes during the recovery period over three days (postoperative days 1 to 3). Pain intensity was measured before and after the intervention using the Numeric Rating Scale (NRS), and behavioral responses were also observed. Results: The VR intervention showed a reduction in pain intensity from moderate (scale 6) to mild (scale 3) in both subjects. Additionally, there was an improvement in behavioral responses, indicated by reduced grimacing, decreased anxiety, increased cooperation, and relaxation during the recovery period. The nursing diagnosis of acute pain was considered resolved. Conclusion: The use of VR can be an alternative non-pharmacological intervention to help reduce pain and improve behavioral responses in children after appendectomy.